PHOTOMETRY OF STARS FOR ASTRONEGATIVES WITH A SINGLE EXPOSURE - Andruk, V.; Eglitis, I.; Protsyuk, Yu.; Akhmetov, V.; Pakuliak, L.; Shatokhina, S.; Yizhakevych, O. (Одеські астрономічні публікації, 2019)
The paper discusses the construction of characteristic curves for various astronegatives with a single exposure. Particular attention is paid to the question of extrapolation of the characteristic curve for the region of the weakest stars in the absence of standards. A new method for constructing an individual characteristic curve for digitized films and plates in the UBVR system has been proposed and implemented. The processing of frames of digitized plates and films with sky areas is car- ried out using LINUX/MIDAS/ROMAFOT software tools. ROMAFOT application allows us to extract astro- metric rectangular coordinates X,Y and photometric char- acteristics such as instrumental photometric magnitudes m, FWHM, and the intensity in the center of the star im- age I c for all fixed objects on each astronegative. For all frames, the connection between instrumental photometric values m with stellar magnitudes in any system (Johnson UBVR, Tycho-2 or GAIA catalogs, etc.) is not linear and multipurpose. It is presented as the characteristic curve for each astronegative. Currently, the determination of U, B, V, R magnitudes of stars and other space objects is in pro- gress for astronegatives with the single exposure obtained in the frameworks of selected observational projects.